Ecophysiology, Vigour, Berry and wine Quality of Grapevines Growing on and off Heuweltjies - Bekker, S.J.; Hoffman, J.E.; Jacobs, S.M.; Strever, A.E.; Van Zyl, J.L. (South African Journal of Enology and Viticulture, 2016)
Heuweltjies are unique landscape features putatively created by the termite Microhodotermes viator through their burrowing and nest-building activities. They have been closely examined in the natural veld of the Western Cape in the recent past and are the focus of many ecological studies, but their effect in cultivated landscapes (e.g. vineyards and orchards) has remained unexplored. This study addresses the vigour and physiology of vines growing on and off heuweltjies, as well as the wine emanating from these vines. This study was conducted on Cabernet Sauvignon and Shiraz in two climatic regions of the Western Cape, namely Stellenbosch (Mediterranean climate) and Robertson (semi-arid climate) respectively, to better understand how differences in heuweltjie characteristics correspond to differences in rainfall and temperature. Through the use of ANOVAs and Fisher’s LSD post hoc tests to indicate statistical significance, it was apparent that the soil on and off heuweltjies differed significantly in respect of several physical and chemical properties. Consequently, soil water content was more favourable on heuweltjies, especially in the Stellenbosch area, where only supplementary irrigation was applied. Heuweltjies induce substantial changes in grapevine vigour and grape composition. Differences in grapevine physiology between heuweltjie and non-heuweltjie plots were subtle, but vine vigour was severely altered on the heuweltjieassociated vines, exhibiting excessive vegetative growth in Stellenbosch and leading to variations in berry and wine characteristics on and off the heuweltjies. The opposite was observed in the semi-arid climate of Robertson. The presence of heuweltjies in vineyards presents an opportunity to produce and market wines with a difference in respect of their characteristics and unique origin.